PERBEDAAN TINGKAT KEPUASAN KERJA AUDITOR PADA LOCUS OF CONTROL INTERNAL DAN EKSTERNAL - Rasuma Putri, Dwiyana; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
The purpose of this study is to analyze the differences level of job statisfaction on the difference locus of control.The data in this study was obtained from auditors who work in public accounting form in Bali Province which has complete and return the questionarie. Questionnaires were distributed are  67 pieces that can be used as a sample for the analysis is 46 pieces. T-test of two independent samples is a data analysis technique used in this study. Auditors who have an internal locus of control have better job satisfaction compared with the auditors who have an external locus of control is the result of this study were seen statistically.
Keywords: locus of control, job statisfaction, Public Accounting Firm